2001
DOI: 10.1016/s0020-7292(01)00587-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of levonorgestrel implant upon TSH and LH levels in male infants during lactation

Abstract: The overall data indicate that the LNG levels transferred to fully breast-fed infants through breast milk from Norplant users significantly modified their TSH levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…24 One recent controlled study found a direct correlation between infant levonorgestrel levels and thyroid-stimulating hormone suppression. 42 It is difficult to judge the relevance of an excess of deaths from gastroenteritis (4), pneumonia (1), or seizure (1) compared to placebo (1 death from gastroenteritis) in a nonrandomized trial of nomegestrol, a progestin unavailable in the United States. 25 Most studies and reviewers have found no adverse effects on lactation or breastfed infants from maternal progestin-only contraceptives.4347 However, the practice of providing injectable or implantable progestin-only contraceptives within a few days postpartum48 has not been adequately studied.…”
Section: Contraceptivesmentioning
confidence: 99%
“…24 One recent controlled study found a direct correlation between infant levonorgestrel levels and thyroid-stimulating hormone suppression. 42 It is difficult to judge the relevance of an excess of deaths from gastroenteritis (4), pneumonia (1), or seizure (1) compared to placebo (1 death from gastroenteritis) in a nonrandomized trial of nomegestrol, a progestin unavailable in the United States. 25 Most studies and reviewers have found no adverse effects on lactation or breastfed infants from maternal progestin-only contraceptives.4347 However, the practice of providing injectable or implantable progestin-only contraceptives within a few days postpartum48 has not been adequately studied.…”
Section: Contraceptivesmentioning
confidence: 99%
“…5 The higher the levonorgestrel levels, the lower the TSH levels in the infants. 5 The higher the levonorgestrel levels, the lower the TSH levels in the infants.…”
Section: Implants and Injectionsmentioning
confidence: 99%
“…Recent evidence suggests that progestins in contraceptives can enter mother's milk, can be detected in the serum of breast-fed infants (2)(3)(4)15), and may influence the infant hypothalamo-pituitary-thyroid axis (16). Yet a recently published meta-analysis of clinical reports concluded that evidence regarding the use of hormonal contraceptive during lactation is limited and of poor quality and stressed the urgent need for a properly conducted clinical trial in this field (17).…”
Section: P Use In Humansmentioning
confidence: 99%